2008
DOI: 10.1007/s10165-008-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of immunoglobulin G4-related chronic sclerosing sialadenitis and dacryoadenitis associated with tuberculosis

Abstract: We describe a 64-year-old woman with chronic sclerosing sialadenitis and dacryoadenitis, which developed during treatment for cervical lymph node tuberculosis. Anti-tuberculosis treatment did not improve the swelling in the lacrimal and submandibular glands, and a biopsy specimen of the lacrimal gland showed inflammation, with abundant lymphoid follicles with fibrosis and granuloma without caseous necrosis. Immunohistological examination of a repeat biopsy specimen showed abundant immunoglobulin (Ig) G4-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…16,21,22,31,32,[34][35][36] Cheuk et al 21 reported 6 cases, 4 women and 2 men with an average age of 45.5 years (SD 18.3, range 24-67). Five of the 6 cases had bilateral disease, and 50% had salivary gland involvement.…”
Section: Discussionmentioning
confidence: 97%
“…16,21,22,31,32,[34][35][36] Cheuk et al 21 reported 6 cases, 4 women and 2 men with an average age of 45.5 years (SD 18.3, range 24-67). Five of the 6 cases had bilateral disease, and 50% had salivary gland involvement.…”
Section: Discussionmentioning
confidence: 97%
“…IgG4-RD occurs comparatively more in the older persons (median age, 58 years), slowly progresses and shows relatively weak inflammation signs such as low titer of CRP ( 1 ). Infections with various species of pathogens such as Helicobacter pylori ( 46 , 47 ), Gram-negative bacteria ( 48 ) and Mycobacterium tuberculosis ( 49 ) have been reported in IgG4-RD. In addition, stimulation with toll-like receptor (TLR) ligands induces production of both IgG4 and IL-10 from PBMCs ( 50 ).…”
Section: Pathogenesis Of Igg4-rdmentioning
confidence: 99%
“…Kawano et al reported a case of IgG4 related chronic sialadenitis and dacryoadenitis in a patient who had been treated for cervical lymph node tuberculosis [29]. Imai et al reported a case of IgG4 related tubulointerstitial nephritis after remission of urinary tract tuberculosis [30].…”
Section: Discussionmentioning
confidence: 99%